AUTONOMOUS ENGLISH VOCABULARY LEARNING THROUGH ENGLISH SUBTITLED: NON-MAJOR ENGLISH EDUCATION STUDENTS’ PERCEPTIONS - Salma Samrotul Habibah (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
In the rapidly advancing digital era, audiovisual media such as films with subtitles can serve as a useful resource for improving English skill independently. This, study investigates the perception of non-major English education students when watching films with English subtitles as a medium for independent vocabulary learning. The research design used a descriptive case study, in this research, three participants from one of the universities in Bandung who were not from English major were involved in this research. The study used semi-structured interviews as collection, and the data which were analyzed thematically. The findings show positive perceptions of non-English major students towards watching movies with English subtitles for independent vocabulary learning: (1) learning engagement, (2) Independent learning strategies, and (3) vocabulary mastery. This shows that watching movies with English subtitles is an effective, flexible, and fun learning tool for non-English Education students. This learning not only improves their language skills independently, but also builds confidence from within.